38.4k views
3 votes
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!

Simplify.

4√27 + 6√75

PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!! Simplify. 4√27 + 6√75-example-1
User Deiga
by
5.3k points

2 Answers

3 votes

To answer this, you will first need to simply the expressions.


4√(27) = 12√(3)


6√(75) = 30√(3)

Now with the expressions simplified, you'll add the two together getting
42√(3)


User Feng Yu
by
5.9k points
3 votes
  • Product rule of radicals: √ab = √a × √b

So firstly, we have to simplify the radicals. Using the product rule of radicals, simplify these radicals as such:

4√27 = 4 × √9 × √3 = 4 × 3 × √3 = 12√3

6√75 = 6 × √5 × √15 = 6 × √5 × √5 × √3 = 6 × 5 × √3 = 30√3

Now, add these two simplified radicals as such:

12√3 + 30√3 = 42√3

42√3 is your final answer.

User Clevison Luiz
by
5.8k points